Risk-Benefit Profile of Gastric vs Transpyloric Feeding in Mechanically Ventilated Patients: A Meta-Analysis. (February 2016) - Li, Zhuo; Qi, Jirong; Zhao, Xiaoke; Lin, Yiqun; Zhao, Shaodong; Zhang, Zendi; Li, Xiaonan; Kissoon, Niranjan
Background: The risk-benefit profile of transpyloric vs gastric feeding in mechanically ventilated (MV) patients has not been definitively established. Objective : To evaluate the risks and benefits of transpyloric feeding compared with gastric feeding in mechanically ventilated patients. Design : We systematically searched MEDLINE, Google Scholar, EMBASE, and the Cochrane Central Register of Controlled Trials databases for eligible articles through June 21, 2013. Randomized controlled trials (RCTs) that reported a comparison between gastric and transpyloric feeding in MV patients were selected. Two reviewers independently extracted data on populations, methods, outcomes, and risk of bias. Ventilator-associated pneumonia (VAP) was considered the primary outcome. Results : A total of 8 RCTs, including 835 MV patients, were identified and analyzed. Our pooled findings indicated that there was a significant reduction in VAP through transpyloric feeding compared with gastric feeding (relative risk [RR], 0.67; 95% confidence interval [CI], 0.53 to 0.85; P = .001) but not in mortality (RR, 1.08; 95% CI, 0.86 to 1.36; P = .49), length of mechanical ventilation (mean difference [MD], –0.16; 95% CI, –0.75 to 0.43; P = .59), length of stay in the intensive care unit (MD, –0.91; 95% CI, –2.75 to 0.94; P = .34), incidence of diarrhea (RR, 0.9; 95% CI, 0.66 to 1.23; P = .50), and incidence of vomiting (RR, 0.82; 95% CI, 0.25 to 2.72; P = .75). Conclusions : Transpyloric feeding in MV adults was associated with significantly less incidence of VAP compared with gastric feeding. No differences were observed in other outcomes, suggesting that the difference observed in the incidence of VAP may be spurious and needs confirmation.